Methods of Financing Technical and Vocational Education and Training, and Entrepreneurship Education to Support Skills Development in Lusaka Province, Zambia - Mubanga, Philip; Hock, Oo Yu; Asif, Mahbub Karim; Mulenga, Innocent Mutale (Research Gate, 2019)
Technical and Vocational Education and Training (TVET), and Entrepreneurship Education are vital components in the economic development equation of any country. However, these training systems can only be effective where sustainable methods of financing TVET and entrepreneurship training are in place. In order to obtain information on the most appropriate methods of funding skills development in the two specific skills categories, it was deemed necessary and important to obtain reliable empirical quantitative and qualitative data from the government officers, the industry experts and administrators in vocational institutions. A questionnaire was administered in all the eight districts of Lusaka Province among purposely selected sixteen TVET administrators. Interviews were conducted with the sixteen purposely selected senior government officers, and sixteen parents of TVET learners selected using snowball sampling. Two respondents were drawn from each respondent group across the eight districts. Since the study adopted a mixed research approach with a concurrent triangulation design, data were analysed through a thematic approach and also utilising descriptive statistics from the Statistical Package for SocialSciences (SPSS). This article focuses on the evaluation of the most appropriate methods of financing TVET,and Entrepreneurship education with the rationale of improving skills development to mitigateunderdevelopment which has mainly contributed to unemployment leading to abject poverty in Lusaka province. The findings of the study revealed seven appropriate methods of financing TVET and Entrepreneurship education. Furthermore, results showed that lack of funding or inadequate funding were cited as some of the causes of poorly resourced vocational institutions leading to inadequate tools, equipment, shortage of teaching materials in vocational schools and low motivation among the teaching staff and other faculty members.